Exploring the experiences of organisational justice in government department in South Africa - Maluleke, Floyd Dimatso (University of the Witwatersrand, Johannesburg, 2024)
The study explored organisational justice experiences in the Department of Trade, Industry and Competition (the dtic) by determining how employees access organisational justice, what motivates employees to take justice-related actions, and employees' overall perception of organisational justice. Semi-structured interviews comprising 15 participants were conducted, while thematic analysis was used to analyse and present the interview data. The study found that organisational justice is accessed through the employee's immediate line manager, the employment relations unit, and organised labour. The study revealed that employees preferred their immediate managers and organised labour due to their support, trust, and interaction quality. Motivation to pursue organisational justice revealed knowledge as a primary motivator for taking justice-related actions, including personality traits requiring access to information. The perception of employees' experiences revealed the presence of bias in procedures, interactions, information, and outcomes and inefficiencies in how the department communicates processes and outcomes, influencing how employees feel about fairness in the department. The perception of employees' overall justice judgment in the department revealed perceived inequality, influenced by a lack of explanations and the inability of the department to consider employee's needs. The findings revealed that fairness is required in all components of organisational justice, with custodians playing a pivotal role in shaping how employees experience and perceive the management of organisational justice in the public sector. Fundamentally, the study revealed that employees can distinguish between what component and justice rules within each component are violated, supporting the need for fairness in each component. The study concluded by providing recommendations and avenues for future research, with the hope that the study's findings can be helpful in internal governance policies and the management of organisational justice.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Organisational Justice; Procedural Justice; Information Justice; Interactional Justice; Outcome Justice; Fairness; SDG-8: Decent work and economic growth